Fe3N‐Co2N Nanowires Array: A Non‐Noble‐Metal Bifunctional Catalyst Electrode for High‐Performance Glucose Oxidation and H2O2 Reduction toward Non‐Enzymatic Sensing Applications. Issue 22 (29th March 2017) - Zhou, Dan; Cao, Xiaoqin; Wang, Zao; Hao, Shuai; Hou, Xiandeng; Qu, Fengli; Du, Gu; Asiri, Abdullah M.; Zheng, Chengbin; Sun, Xuping
Abstract: Among reported electrode materials, a nanoarray is an attractive architecture for molecular detection because of its large specific surface area and easy accessibility for target molecules. Here, a new Fe3 N‐Co2 N nanowires array grown on carbon cloth (Fe3 N‐Co2 N/CC) is reported as a non‐noble‐metal bifunctional catalyst electrode for high‐performance glucose oxidation and H2 O2 reduction. As an electrochemical non‐enzymatic sensor for glucose detection, Fe3 N‐Co2 N/CC shows a fast response time of 8 s, a low detection limit (LOD) of 77 nm (signal/noise=3), and a high sensitivity of 4333.7 μA mm −1 cm −2 . As an H2 O2 sensor, it shows a LOD of 59 nm (signal/noise=3) and a sensitivity of 2273.8 μA mm −1 cm −2 with a response time of 2 s. In addition, the proposed sensor is stable with high selectivity, specificity, and reproducibility, and its application for real sample analysis has been successfully demonstrated. Abstract : A Fe3 N‐Co2 N nanowires array behaves as a non‐noble‐metal bifunctional catalyst electrode for high‐performance glucose oxidation and H2 O2 reduction and, thus, selective non‐enzymatic detection. For glucose detection, it shows a low detection limit (LOD) of 77 nm (signal/noise=3) and a sensitivity of 4333.7 μA mm −1 cm −2 . As an H2 O2 sensor, it shows an LOD of 59 nm with a sensitivity of 2273.8 μA mm −1 cm −2 .